Exploring the impact of internet gaming disorder on adolescent gamers using thematic analysis - Deena Balakrishnan, Dr. Sonia George (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Most of the top gaming companies are owned by China, Japan, Korea, and USA. However, the users of games, developed by these gaming tech-giants are worldwide. Online/offline gaming has been a fascination for adolescents and adults ever since video games came in the global market. Moreover, Internet provides a plethora of online and offline games which help the gamers to vent out their feelings and extend resources through communication which is essential for a healthy development of emotional and psychological state. Though society often took gaming as a light hearted activity and often intended to reduce stress and boredom has recently taken a drastic shift, highlighting its negative outcomes on the users. To add on to this, the formal declaration of Internet gaming as a mental health disorder by the World Health Organization (WHO) 2018 has brought relentless researches focusing on the detrimental impact of Internet games on the users. Moreover, this inclusion has had a great influence on the scientific researches. This paper attempts to explore the impact of Internet Gaming Disorder (IGD) on adolescent gamers qualitatively using thematic analysis, and offers suggestion for combating issues pertaining to Internet games on its users.